2018
DOI: 10.1111/jace.15479
|View full text |Cite
|
Sign up to set email alerts
|

Zirconium carbide oxidation: Kinetics and oxygen diffusion through the intermediate layer

Abstract: Oxidation of hot‐pressed ZrC was investigated in air in the 1073‐1373 K range. The kinetics were linear at 1073 K, whereas at higher temperature samples initially followed linear kinetics before undergoing rapid oxidation leading to a Maltese cross shape of the oxide. The linear kinetics at 1073 K was governed by inward oxygen diffusion through an intermediate layer of constant thickness between ZrC and ZrO2 which was comprised of amorphous carbon and ZrO2 nanocrystals. Diffusion of oxygen through the intermed… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 57 publications
(25 citation statements)
references
References 51 publications
2
23
0
Order By: Relevance
“…ZrC commercial powder has, according to the manufacturer, a carbon content of 11.6 wt% (11.1% being combined and 0.5% being free carbon). The ZrC commercial powder analysed with the equipment used for this study showed a carbon content of 11.7 ± 0.1 wt% 35 , in line with the manufacturers' specifications. As described in our previous work 35 the hot pressed ZrC x pellets from Set A had a carbon content of 11.2 ± 0.1 wt%, while pellets from Set B had a carbon content of 11.9 ± 0.1 wt%.…”
Section: Inert Gas Fusion Stoichiometry Of Set a And Set B Was Reasssupporting
confidence: 78%
See 1 more Smart Citation
“…ZrC commercial powder has, according to the manufacturer, a carbon content of 11.6 wt% (11.1% being combined and 0.5% being free carbon). The ZrC commercial powder analysed with the equipment used for this study showed a carbon content of 11.7 ± 0.1 wt% 35 , in line with the manufacturers' specifications. As described in our previous work 35 the hot pressed ZrC x pellets from Set A had a carbon content of 11.2 ± 0.1 wt%, while pellets from Set B had a carbon content of 11.9 ± 0.1 wt%.…”
Section: Inert Gas Fusion Stoichiometry Of Set a And Set B Was Reasssupporting
confidence: 78%
“…The ZrC commercial powder analysed with the equipment used for this study showed a carbon content of 11.7 ± 0.1 wt% 35 , in line with the manufacturers' specifications. As described in our previous work 35 the hot pressed ZrC x pellets from Set A had a carbon content of 11.2 ± 0.1 wt%, while pellets from Set B had a carbon content of 11.9 ± 0.1 wt%. The stoichiometry of Set A and Set B from elemental analysis was reported as all other impurities were measured (oxygen and nitrogen) and an accurate (global) C/Zr atomic ratio could be estimated.…”
Section: Inert Gas Fusion Stoichiometry Of Set a And Set B Was Reasssupporting
confidence: 78%
“…However, nonisothermal oxidation studies related to the formation of SiO 2 and MoO 3 during MoSi 2 oxidation is scarce in the literature. Also, several research groups investigated the oxidation stability of a variety of materials through the TGA/DTG/DTA technique using an air atmosphere . So, it is crucial to study the nonisothermal oxidation behavior of MoSi 2 through the TGA/DTG/DTA technique.…”
Section: Resultsmentioning
confidence: 99%
“…The oxidation behaviour of ZrC has been investigated in several studies on powder samples [13][14][15]19,20], as well as bulk materials [16,17,[21][22][23][24][25][26] and CVD coatings [15]. The oxidation mechanism of this system is generally described by the initial formation of a ZrCxOy phase, followed by the occurrence of amorphous or nanocrystalline ZrO2 [13][14][15][16][25][26][27]. This ZrO2 phase acts as an oxygen diffusion barrier and retards the oxidation process, leading to the precipitation of free carbon.…”
Section: Introductionmentioning
confidence: 99%